Military Expenditure : Econometric Testing of Economic and Political Influences - Hewitt, Daniel (IMF Working Papers; Working Paper ;, 1991)
Econometric results from an analysis of the determinants of military expenditure in 125 countries during 1972-88 are presented. The dependent variable is the ratio of military expenditure to GDP; included among the explanatory variables are economic and financial indicators, political variables summarizing the form of government, and demographic and geographic features of nations. The results strongly confirm the importance of these variables in explaining cross-country differences in levels of military expenditure.